Exceptions to the rule of informed consent for research with an intervention. Issue 1 (December 2016) - Rebers, Susanne; Aaronson, Neil; van Leeuwen, Flora; Schmidt, Marjanka
Abstract Background In specific situations it may be necessary to make an exception to the general rule of informed consent for scientific research with an intervention. Earlier reviews only described subsets of arguments for exceptions to waive consent. Methods Here, we provide a more extensive literature review of possible exceptions to the rule of informed consent and the accompanying arguments based on literature from 1997 onwards, using bothPubmed andPsycINFO in our search strategy. Results We identified three main categories of arguments for the acceptability of a consent waiver: data validity and quality, major practical problems, and distress or confusion of participants. Approval by a medical ethical review board always needs to be obtained. Further, we provide examples of specific conditions under which consent waiving might be allowed, such as additional privacy protection measures. Conclusions The reasons legitimized by the authors of the papers in this overview can be used by researchers to form their own opinion about requesting an exception to the rule of informed consent for their own study. Importantly, rules and guidelines applicable in their country, institute and research field should be followed. Moreover, researchers should also take the conditions under which they feel an exception is legitimized under consideration. After discussions with relevant stakeholders, a formal request should be sent to an IRB.